Chylolymphatic mesenteric cysts in early infancy: case reports and literature review - Soni, Swetha E.; Sharma, Vibhu; Bhaisare, Shital N.; Soni, Mayur S. (International Journal of Contemporary Pediatrics, 2026)
Chylolymphatic mesenteric cysts are an uncommon entity in infancy and represent a rare but important cause of intestinal obstruction. We report two infant cases, one arising from the jejunal mesentery and the other from the ileal mesentery, both presenting with progressive abdominal distension and recurrent vomiting. Ultrasonography and intraoperative findings suggested mesenteric cystic lesions causing bowel obstruction. Complete surgical excision of the cysts with resection of the involved bowel segments and primary anastomosis was performed in both cases. The postoperative course was uneventful, and both infants recovered well without recurrence. Early recognition and complete excision are crucial to prevent complications and ensure excellent surgical outcomes.